POLA ASUH ANAK DALAM LINGKUNGAN KELUARGA POLRI (STUDI DI ASRAMA POLDA RIAU PEKANBARU) - Keke Dwi Sundari; Yusmar Yusuf (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Pattern foster the maintenance of a child that is how parents treat, educate, guide and discipline and protecting the child. Based on the above, then the problem can be formulated as follows: